Influence of the Crystalline State on Photoinduced Dynamics of Photoactive Yellow Protein Studied by Ultraviolet-Visible Transient Absorption Spectroscopy - Yeremenko, Sergey (Biophysical Society, 2006)
Time-resolved ultraviolet-visible spectroscopy was used to characterize the photocycle transitions in single crystals of wild-type and the E-46Q mutant of photoactive yellow protein (PYP) with microsecond time resolution. The results were compared with the results of similar measurements on aqueous solutions of these two variants of PYP, with and without the components present in the mother liquor of crystals. The experimental data were analyzed with global and target analysis. Distinct differences in the reaction path of a PYP molecule are observed between these conditions when it progresses through its photocycle. In the crystalline state i), much faster relaxation of the late blue-shifted photocycle intermediate back to the ground state is observed; ii), this intermediate in crystalline PYP absorbs at 380 nm, rather than at 350–360 nm in solution; and iii), for various intermediates of this photocycle the forward reaction through the photocycle directly competes with a branching reaction that leads directly to the ground state. Significantly, with these altered characteristics, the spectroscopic data on PYP are fully consistent with the structural data obtained for this photoreceptor protein with time-resolved x-ray diffraction analysis, particularly for wild-type PYP.